Instilling Islamic Religious Education Values by Implementing an Honesty Canteen for Students at Darunnajah Middle School - Nursyamsiyah, Siti; Huda, Hairul; Halid, Ahmad; Ramlan, Siti Rosilawati (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2025)
at the Madrasah Tsanawiyah Darunnajah Jember school, an honesty canteen was formed to instill the value of Islamic religious education, namely the value of honesty. Honesty canteen is a program held in schools based on a form of concern for students so that they become a generation of the nation who are knowledgeable and have morals, namely by selling goods needed by students in the form of school equipment such as notebooks, pencils, pens, rulers, food, drinks, and others. This research uses a qualitative approach, data collection is carried out through interviews, observation, and documentation. Based on the research results, the honesty canteen is conceptualized and managed carefully, the payment system is carried out by the buyer himself, namely by putting money into the box provided without being supervised by the canteen guard. So this honesty canteen really relies purely on the honesty of each student. This honesty canteen has many positive impacts that can be accepted and instilled in each individual student, namely being able to train the level of honesty possessed by each student, training students' discipline and responsibility, and being able to instill an anti-corruption spirit in students.